Avian diversity in river levee forest: the effect of microscale heterogeneity - Brarda, Carolina Antonella; Manzano, Adriana Silvina; Piña, Carlos Ignacio; Frutos, Antonio Esteban (Revista de biología tropical, 2024)
Introduction: Levee forests exhibit a vertical stratification that may contribute to structural complexity allowing a great diversity of birds to thrive on the islands. In deltaic ecosystems there is scarce or no data to prove it. Objectives: To assess variations in the composition of the bird community within levee forests. Methods: Two areas of protected wetlands belonging to the Paraná River Delta in Argentina were sampled for three years. A comparative analysis of richness, abundance, and diversity was performed in different levee forests using the point count method. Results: Three distinct types of levee forests -open, intermediate, and closed- were identified based on the structure of their vegetation, hosting a total of 85 bird species. Variation in avian community structure among forest types revealed greater diversity in open forests during winter (3.26 ± 0.13, P < 0.01) and spring (3.58 ± 0.05, P < 0.01), and greater richness in autumn (35.33 ± 3.01, P < 0.01). The closed forests exhibited increased diversity during autumn (3.16 ± 0.13, P < 0.05) and summer (3.24 ± 0.06, P < 0.05), along with elevated abundance in autumn (114 ± 13.70, P < 0.05) and richness in spring (39.17 ± 4.71, P = 0.01). Due to the evolutionary history between sites, significant variation was observed in the most recently created national park, influencing abundance in winter (141 ± 22.06, P < 0.01) and spring (176 ± 12.83, P < 0.01), as well as diversity in winter (3.25 ± 0.10, P < 0.01) and spring (3.50 ± 0.10, P < 0.01). Conclusions: The microhabitat in the different levee forests allows the birds to organize differently. Focusing on microspatial dynamics is key to a deep understanding of the biological processes within subtropical islands and to plan conservation strategies and demonstrate the transition of a recovering riparian forest towards its natural state, where the pulse of the river and the effect of seasonality do not stop operating.